2022
DOI: 10.1186/s12302-022-00668-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characterization of aerosols and trace gases over the Yangtze River Delta region, China: impact of trans-boundary pollution and meteorology

Abstract: Background The spatiotemporal variation of observed trace gases (NO2, SO2, O3) and particulate matter (PM2.5, PM10) were investigated over cities of Yangtze River Delta (YRD) region including Nanjing, Hefei, Shanghai and Hangzhou. Furthermore, the characteristics of different pollution episodes, i.e., haze events (visibility < 7 km, relative humidity < 80%, and PM2.5 > 40 µg/m3) and complex pollution episodes (PM2.5 > 35 µg/m3 and O3 > 160 µg/m3) were studied over the cities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…These results indicate that air pollution control measures in eastern Xinjiang have achieved some effectiveness in recent years, but the PM concentrations in eastern Xinjiang remain at high levels, possibly due to its unique geographic location, frequent dust storms, and the influence of regional transport. [41,42]. Therefore, coarse particles from dust emissions are the main cause of PM pollution in eastern Xinjiang [43].…”
Section: Air Quality and Main Pollutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results indicate that air pollution control measures in eastern Xinjiang have achieved some effectiveness in recent years, but the PM concentrations in eastern Xinjiang remain at high levels, possibly due to its unique geographic location, frequent dust storms, and the influence of regional transport. [41,42]. Therefore, coarse particles from dust emissions are the main cause of PM pollution in eastern Xinjiang [43].…”
Section: Air Quality and Main Pollutantsmentioning
confidence: 99%
“…Some studies have shown that the atmospheric boundary layer height in the Xinjiang region exhibits a distinct unimodal variation, gradually increasing during the daytime and decreasing during the nighttime [48,49]. Therefore, these variations are [41,42]. Therefore, coarse particles from dust emissions are the main cause of PM pollution in eastern Xinjiang [43].…”
Section: Diurnal Weekly and Monthly Variationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, weather conditions could be different in different locations within one city. Limited studies in Hangzhou using official or remote sensing data could not accurately obtain such data for the monitoring sites [3,23,24]. Hence, first-hand monitoring data near the emission source, including meteorological factors, is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Tropospheric O 3 formation is a complex process that depends on precursor species and several other factors. The COVID-19 pandemic and subsequent lockdown measures resulted in emission reductions of VOCs and NO x , but O 3 concentrations still increased in many regions [14][15][16]. Recent studies suggest this is due to the various factors (e.g., aerosols, meteorology and pollution source distribution) that govern atmospheric O 3 formation [12,17].…”
Section: Introductionmentioning
confidence: 99%